The Role of Hysterosonography in Uterine Lesion Detection: A Study Comparing its Accuracy with Hysteroscopy - Mahwish Rizwan, Zanobia Waseem, Amina Hameed, Yaman Shahid, Farah Naz, Aisha Aslam (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To evaluate the diagnostic accuracy of hysterosonography (HSN) in detecting uterine lesions by comparing its findings with hysteroscopy, the gold standard. Methods: A total of 140 women who presented with symptoms suggestive of uterine lesions, including abnormal uterine bleeding or infertility, were enrolled in the study. Each patient underwent hysterosonography followed by hysteroscopy. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of hysterosonography were calculated using SPSS 24.0, with the p-value for statistical significance set at <0.05. Results: The sensitivity of hysterosonography was 92% for detecting endometrial polyps and 85% for detecting fibroids. The specificity was 89% for polyps and 84% for fibroids. The overall diagnostic accuracy of hysterosonography was 88%. False positives were observed primarily in cases of uterine adhesions, while false negatives were seen in submucosal fibroids. The p-value for the comparison between hysterosonography and hysteroscopy was 0.04, indicating statistical significance. Conclusion: Hysterosonography is a reliable and effective diagnostic tool for detecting uterine lesions, particularly endometrial polyps and fibroids. Its non-invasive nature, combined with high sensitivity and specificity, makes it a valuable tool for initial screening, although hysteroscopy remains the definitive diagnostic method. Keywords: Hysterosonography (HSN), Uterine lesions, Endometrial polyps, Fibroids, Abnormal uterine bleeding (AUB), Infertility, Hysteroscopy, Diagnostic accuracy